OPTIMALISASI PERTUMBUHAN DAN HASIL PADI (Oryza sativa L.) MELALUI INTERAKSI BIOCHAR BERLAPIS ASAM HUMAT DAN JARAK TANAM - Anggarbeni, Susilo Ribut; Padaka, Meryana; Hamzah, Amir (BUANA SAINS, 2025)
Land degradation challenges rice productivity in Indonesia, demanding innovative agronomic solutions. This study evaluated the interaction between humic acid-coated biochar rates and plant spacing on the growth and yield of rice (var. IR-64). A field experiment using a factorial Randomized Complete Block Design was conducted in Malang. The treatments used a 2 factorial, the first factor included four biochar rates (0, 5, 10, and 15 t ha⁻¹) and the second factor used three plant spacings (20x20, 20x30, and 20x40 cm). The result showed a significant interaction (P 0.05) between biochar rate and spacing for the number of tillers and stem diameter. The highest tiller count (35.27) was recorded in the 5 t ha⁻¹ biochar rate, combined with 20x40 cm spacing. While the main effect of biochar on yield was not significant, plant spacing had a dominant impact; the 20x30 cm spacing yielded the highest grain weight per plot (8.74 kg). These findings highlight that rice yield optimization depends on the specific synergy between soil ameliorants and planting density